Practical Reflection and Benefits of Making a Food Garden at Home During Covid-19 Pandemic - Aditya, Rendy Bayu; Zakiah, Aisyah (2022)
The partial lockdown during the Covid-19 pandemic in Indonesia pushed people to work from and spend more time at home. During this unprecedented time, many people pursued new hobbies in gardening, which proved to enhance physical and mental health. With anxieties regarding food insecurity, food gardens became a new urban trend. With a relatively tiny space available, it is possible to make an urban food garden in the front yard of a house using various cultivation techniques to maximize space. However, the implementation of food gardens in urban houses is quite challenging due to limited space. Then, we reflect on the practical process and personal benefits gained from developing a tiny food garden at home. The tiny food garden could produce a variety of vegetables and herbs, such as the spinach family, lettuce, Asian greens, the tomato family, eggplants, the basil family, mint, rosemary, moringas, and butterfly-pea flowers. It may support a household with few amounts of fresh emergency food in the worst scenario during the Covid-19 pandemic. Besides, developing a tiny food garden at home may also provide co-benefits such as enhanced subjective well-being, increased appreciation of food and the environment, motivating others to start gardening at home, and great personal satisfactions of consuming home-grown food. With all these socio-ecological co-benefits, home food garden must be integrated as a strategy to achieve urban sustainability and increase household food resilience. © 2022. ISEKI-Food Association (IFA)